2022
DOI: 10.1038/s41467-022-31764-9
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia induces HIF1α-dependent epigenetic vulnerability in triple negative breast cancer to confer immune effector dysfunction and resistance to anti-PD-1 immunotherapy

Abstract: The hypoxic tumor microenvironment has been implicated in immune escape, but the underlying mechanism remains elusive. Using an in vitro culture system modeling human T cell dysfunction and exhaustion in triple-negative breast cancer (TNBC), we find that hypoxia suppresses immune effector gene expression, including in T and NK cells, resulting in immune effector cell dysfunction and resistance to immunotherapy. We demonstrate that hypoxia-induced factor 1α (HIF1α) interaction with HDAC1 and concurrent PRC2 dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 62 publications
1
40
0
Order By: Relevance
“…Hypoxic effects on immune cells also lead to insufficient PD‐L1 and PD‐L2 responses. 110 Targeting HIF‐1α with drugs or genes can inhibit PD‐L1 expression in the TME and enhance interferon production by T cells. 111 , 112 , 113 Targeting HIF‐1α reverses immune dysfunction and overcomes resistance to PD‐L1 blockade.…”
Section: The Role Of Hypoxia In Tumor Progressionmentioning
confidence: 99%
“…Hypoxic effects on immune cells also lead to insufficient PD‐L1 and PD‐L2 responses. 110 Targeting HIF‐1α with drugs or genes can inhibit PD‐L1 expression in the TME and enhance interferon production by T cells. 111 , 112 , 113 Targeting HIF‐1α reverses immune dysfunction and overcomes resistance to PD‐L1 blockade.…”
Section: The Role Of Hypoxia In Tumor Progressionmentioning
confidence: 99%
“…A study of exhausted CD8+ T cells in humans and a chronic viral infection mouse model by Sen et al revealed that a state-specific epigenetic landscape organized into functional modules of enhancers is required for exhaustion [ 124 ]. Using an in vitro system that models human T cell exhaustion, our data recently reported that hypoxia in the TME induces transcriptional suppression of the immune effectors IFN-γ, tumor necrosis factor α (TNFα), and granzyme B, resulting in immune effector cell dysfunction and resistance to immunotherapy [ 128 ]. Furthermore, the chromatin remodeling enforced by HIF1α interaction with HDAC1 and subsequent dependence on PRC is identified as a crucial epigenetic mechanism conferring immune effector suppression.…”
Section: Stromal Mechanisms Reshaping the Tme And Tumor Immune Responsementioning
confidence: 99%
“…As an environmental stimulator, hypoxia has a conflicting effect on anti-tumor immunity. Effector T cells would undergo epigenetic reprogramming upon hypoxia exposure, and the altered epigenetic regulation reduces their transcription and function ( Ford et al, 2022 ; Ma et al, 2022 ). In contrast, another study demonstrated that hypoxia-inducible factor-1α (HIF-1α) deletion led to the reduction in T cell infiltration and tumor killing during hypoxia conditions ( Palazon et al, 2017 ).…”
Section: The Glucose Metabolism Features In Tumor Microenvironmentmentioning
confidence: 99%